2020
DOI: 10.1161/jaha.120.016479
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Hypergravity Activates Hemostasis in Healthy Volunteers

Abstract: Background Hypergravity may promote human hemostasis thereby increasing thrombotic risk. Future touristic suborbital spaceflight will expose older individuals with chronic medical conditions, who are at much higher thromboembolic risk compared with professional astronauts, to hypergravity. Therefore, we tested the impact of hypergravity on hemostasis in healthy volunteers undergoing centrifugation. Methods and Results We studied 20 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
2
1
Order By: Relevance
“…Consistent with other + Gz studies [39][40][41][42] , our study observed leukocytosis and hemoconcentration in both groups. However, the extent of plasma volume reduction was not as pronounced as in other studies 43 . The leukocytosis observed was likely catecholamine-induced due to splenic release and leukocyte mobilization.…”
Section: Leukocytic and Hematological Reactionscontrasting
confidence: 73%
“…Consistent with other + Gz studies [39][40][41][42] , our study observed leukocytosis and hemoconcentration in both groups. However, the extent of plasma volume reduction was not as pronounced as in other studies 43 . The leukocytosis observed was likely catecholamine-induced due to splenic release and leukocyte mobilization.…”
Section: Leukocytic and Hematological Reactionscontrasting
confidence: 73%
“…In model experiments on small animals, it was shown that the intensity of platelet adhesion and aggregation was reduced after hypogravity and increased after hypergravity exposure 34 . The platelet activation after hypergravity exposure (15 min, 3 Gz) was also observed 35 .…”
Section: Resultsmentioning
confidence: 91%
“…Following spaceflight, a return to activity in a 1 G gravitational field may also constitute a VT risk factor. Indeed, changes in G-loading have been demonstrated to be high risk periods, with brief periods of hypergravity activating haemostasis in healthy volunteers 16 . However, the only documented VT to date in spaceflight was undetectable upon landing, and was discovered months after the hypergravity of launch 1 .…”
Section: Venous Thrombus In Space: What Do We Know? Vt Pathophysiolog...mentioning
confidence: 99%